ON THE ISSUE OF ASSESSING THE TOXICITY RISK OF FORTIFICANT FOR STAPLE FOODS - Olga L. Elinskaya; Natalia V. Voronina; Jakhongir O. Khamdamov (Central Asian Journal of Medicine, 2023)
The most promising solution to the problem of micronutrient deficiency is the enrichment of mass consumption products with missing vital micronutrients, in particular fortifiers. The aim of the research was to assess the risk of toxicity of the Vitamin & Mineral Premix fortificant (vitamin and mineral premix), manufactured by AQC Chemlab Private Limited, India, when used on experimental animals after intragastric administration. The research was carried out in accordance with the legislative and regulatory and methodological documentation. Biochemical blood tests were performed on a semi-automatic biochemical analyzer "CYANSmart" with software (Cypress Diagnostics, Belgium) according to standard methods. A detailed analysis of peripheral blood was determined in the Goryaev chamber. Experimental tests were carried out in compliance with the rules adopted by the European Convention for the Protection of Vertebrates for Experiments or Other Scientific Purposes (ETS No. 123. Strasbourg, 1986). According to the results of toxicological studies, the tested fortifier "Vitamin & Mineral Premix" (vitamin and mineral premix), manufactured by AQC Chemlab Private Limited, India, does not have a negative effect on the health of experimental animals in the intragastric route of admission, according to the parameters of acute toxicity, it refers to low-hazard substances, does not have a cumulative, irritating effect on the mucous membranes of the eyes, sensitizing effect and does not cause pathological and structural changes in the internal organs of experimental animals. This fortifier meets the safety requirements in terms of toxicological indicators.